Simple Modifications of Visuals can Enhance Spatial Orientation Ability in Virtual Environments, Whereas Adding Physical Rotations May Not - Riecke, B. E; Sigurdarson, Salvar (54th Annual Meeting of the Psychonomic Society (Psychonomics), 2013)
Prior research suggests that human spatial orientation (in real and virtual environments) is severely impaired if physical motion cues are missing, to a point that visually simulated rotations in Virtual Reality are not updated (Klatzky et al., 1998), indicating "non-turner" behavior. Using a paradigm similar to Klatzky, participants viewed visually displayed passive movements through an optic flow field (with and without matching physical rotations) before pointing to the invisible origin. While adding physical rotations did not provide any benefit, replacing optic flow with a naturalistic yet landmark-free city environment reduced updating failures from 35% to 10% of trials. Even adding minimal structure to the optic flow environment by drawing the path on the ground reduced task difficulty and decreased updating failures by more than half (35% to 15% of trials). Results suggest that physical motions do not necessarily enhance spatial orientation ability, although even simple modifications of the visuals can.
Keywords: Riecke; Riecke_2013; bernhard-riecke; egocentric; frame; framework; iat812; iat812_spring2011; interference; model; orientation; point-to-origin; posterWithoutPaper; reference; salvar-sigurdarson; spatial; talkWithoutPaper; theory; updating